Utilizing Internet Search Volume to Monitor Stages of Change in Vaccine Hesitancy During the COVID-19 Outbreaks - Lan, Yu-Tung; Wu, Shiow-Ing; Lin, Yu-Hsuan (Frontiers in Public Health, 2022)
Real-time vaccine hesitancy surveillance is needed to better understand changes in vaccination behaviors. To understand the association between COVID-19 outbreaks and population vaccine hesitancy and to monitor the dynamic changes in vaccination behaviors. We used autoregressive integrated moving average model to examine the association between daily Internet search volume for vaccine and two waves of COVID-19 local outbreaks in Taiwan from March 19 to May 25, 2021. During the small-scale outbreak, the search volume increased significantly for 7 out of 22 days with an average increase of 17.3% ± 10.7% from the expected search volume. During the large-scale outbreak, the search volume increased significantly for 14 out of 14 days, with an average increase of 58.4% ± 14.7%. There was a high correlation between the search volume and the number of domestic cases (r=0.71, P<.001). Google Trends serves as a timely indicator to monitor the extent of population vaccine willingness.